Government Capital Expenditure and Economic Growth in Nepal (The Mega Journal, 2023)
This paper explores the short-run and long-run causal relationship between government expenditure, labor force, gross investment, aggregate consumption, and economic growth of Nepal. The gross domestic product (Y), capital expenditure (K), population (L), gross investment (GI), and aggregate consumption (CO) have been used to find the causal relationship between government expenditure, and economic growth. The ARDL cointegration technique confirms a long-run association among the variables. The study revealed that capital expenditure, labor force participation, gross investment, and aggregate consumption all are the long-run driver of the economic growth of Nepal. These findings tell that efficient and timely allocation and use of capital expenditure, expansion of public as well private investment, and increased aggregate consumption matters for economic growth. The study also shows the existence of unidirectional causation from capital expenditure to growth and bidirectional relationship between other variables. The findings support Keynesian thought of government expenditure and economic growth. The regulatory and policymakers should focus on expansionary fiscal policy to stimulate capital formation, efficient productive investment, boost effective demand, and enhance long-run economic growth in Nepal.